Synergizing Green Marketing and Product Innovation: Strategies for Elevating Consumer Choices - Kholifah, Siti Kholifah; Yuswono, Irawan (Pt. Anagata Sembagi Education, 2024)
This study examines the impact of green marketing and green product innovation on brand image and purchasing decisions among consumers. Utilizing a quantitative approach, data were collected from 165 respondents through surveys in Semarang, Indonesia. The findings reveal that green marketing significantly enhances brand image, suggesting that environmentally friendly marketing efforts are valued by consumers and contribute to a positive brand perception. However, green product innovation alone does not significantly affect brand image, indicating the necessity of combining it with effective green marketing strategies. Furthermore, the study confirms that a strong brand image significantly influences purchasing decisions, highlighting the importance of consumer perceptions in driving buying behavior. Green product innovation also shows a significant positive impact on purchasing decisions, demonstrating that eco-friendly and innovative products appeal to consumers. Despite these benefits, green marketing alone does not significantly impact purchasing decisions, suggesting that additional factors are required to drive consumer purchases directly. The study concludes that an integrated strategy combining green marketing and product innovation offers the greatest potential for enhancing brand image and influencing consumer behavior, providing valuable insights for managers seeking to leverage sustainability in their marketing strategies.